Interpretation of Hadith Regarding Ihtikar (Monopoly) In the Perspective of Contemporary Sharia Economic Law - Elma Kamala; HM. Ridlwan Hambali; Ayu Nur Chamidah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract The current global economy faces serious challenges in market mechanisms, including the dominance of large corporations, supply chain distortions, price manipulation, and distribution control by certain entities. This phenomenon bears substantive similarity to the concept of ihtikar in Islam, namely the act of withholding goods to create scarcity and raise prices, thereby causing hardship for the community. Prophetic traditions (ḥadīth) such as